Development on Smart Killer Bacteria - Mohamad, Z.; Omar, W. R. W.; Rudi, M. A.; Shafekah, N.; Daud, E.; Kamaruddin, N.; Rosdi, M.; Zakaria, R. (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2021)
Nowadays, in globalization era there is always the foundation of the new technologies features every year. Smart Bacteria Killer (SBK) become the most popular features which rapidly gaining its popularity due to its importance to certain applications. The lack of system of cleanliness among doctors, nurses and visitors which expose the patients to illness have been an idea to create the device. The device is designed to create a more attractive and appealing design with low cost and affordable. The SBK development is to kill bacteria on hands of users. This tool is designed to help doctors, nurses, patients and visitors to feel comfortable and clean while visit patient, friends or relatives. The lack of system of cleanliness among doctors, nurses and visitors which expose the patients to illness have been an idea to create the device. The device is designed to create a more attractive and appealing design with low cost and affordable. The SBK required a safety ultraviolet lamp with a wavelength of 246nm to kill bacteria. The SBK can be used to all the users such as doctors, nurses, patients and visitors at the hospital for hygiene and cleanness and also free from bacteria.